Ocean circulation and climate at the Eemian and last glacial inception - Born, Andreas (Climate Dynamics, 2010)
Combining a hierarchy of climate models of varying complexity with marine proxy data, we show that the North Atlantic surface circulation played an important role for the climate of the Eemian and the last glacial inception. As insolation decreases, increasing Arctic sea ice export causes a freshwater transport into the subpolar North Atlantic. Amplified by a nonlinear response of the subpolar gyre this leads to a reorganization of the surface currents and a stronger heat transport into the Nordic Seas. The resulting warming of this region delayed Scandinavian inception. This work introduces a relatively new concept into the field of paleoceanography: the subpolar gyre as an active component of the climate system. This is based on recent advances in physical oceanography and allows for a new and physically consistent interpretation of proxy data. Moreover, the sensitivity of the subpolar gyre to different boundary conditions is discussed, improving the understanding of the underlying mechanism.